2023
DOI: 10.1186/s12913-023-09462-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic evaluations of natalizumab, rituximab, and ocrelizumab for the management of relapsing-remitting multiple sclerosis in Saudi Arabia

Abstract: Introduction The advent of new disease-modifying therapies (DMTs), such as monoclonal antibodies (mAbs), resulted in significant changes in the treatment guidelines for Multiple sclerosis (MS) and improvement in the clinical outcomes. However, mAbs, such as rituximab, natalizumab, and ocrelizumab, are expensive with variable effectiveness rates. Thus, the present study aimed to compare the direct medical cost and consequences (e.g., clinical relapse, disability progression, and new MRI lesions)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…The only previous cost-effectiveness studies of rituximab in MS were two smaller observational studies from Saudi Arabia (including 146 and 93 patients, of which 12 and 26 were treated with rituximab, respectively) and 2 simulation studies from Iran and Thailand, respectively. [28][29][30][31] Although severely limited by their size or use of simulation instead of real-world data, the results were broadly in line with our findings. Additionally, a study by a US healthcare provider indirectly assessed the cost-effectiveness of rituximab as part of the evaluation of their MS treatment optimization program.…”
Section: Discussionsupporting
confidence: 88%
“…The only previous cost-effectiveness studies of rituximab in MS were two smaller observational studies from Saudi Arabia (including 146 and 93 patients, of which 12 and 26 were treated with rituximab, respectively) and 2 simulation studies from Iran and Thailand, respectively. [28][29][30][31] Although severely limited by their size or use of simulation instead of real-world data, the results were broadly in line with our findings. Additionally, a study by a US healthcare provider indirectly assessed the cost-effectiveness of rituximab as part of the evaluation of their MS treatment optimization program.…”
Section: Discussionsupporting
confidence: 88%
“…In this review, 3 studies evaluated the cost-effectiveness of rituximab and showed RRMS patients receiving rituximab had lower costs and more QALYs when compared with natalizumab [29,62]. Smet et al in the Netherlands suggested rituximab would already be the most cost-effective anti-CD20 mAb if its efficacy on 6-month CDP is comparable to traditional first-line therapies such as interferon-beta but there are no accurate estimates of rituximab's effect on disability progression [53].…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, symptom management [63] and BSC [22] strategies were analyzed in addition to these two forms of medications. Three study analyzed only intravenous infusions DMDs for RMS [29,43,61,62] (Table 2).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%